Protection of Data Base Security via Collaborative Inference Detection (International Journal of Engineering and Computer Science, 2017)
- In many applications like Defense department, Commercial departments and Marketing departments we need a strongly secured database. Database securities are needed in order to protect our identity and authentication process of users. We propose a novel security mechanism to overcome inference problems and risks for securing the database. Our approach is used for the violation inference detection for single users and multi users. An agent is located between the user input query and the database. Our approach can be used for both the single user as well as the multiple users. This process achieves high authorization, communication accuracy and trust in communication and preventing data from leakage by inference. Here Work is focused on employee information access. Probability of each employee goes on increasing on each query request. When a user poses a query, detection system will examine users past query log for last three days and calculates probability. If probability exceeds than the specified threshold, the query will be denied for that day. Also, to monitor activities, security officer can generate log.